The key role of quoted spreads in financial services and transactions - Peña, Guillermo (Economics and Business Letters, 2021)
Banking has driven the development of the world for centuries. An interesting issue to analyze is the optimal spread on financial products reflecting the value added that does not generate economic distortions for consumers in intertemporal decisions. Based on a gravity equation for these services, this paper examines the optimality of a modified Quoted Spread, the recently-proposed mobile-ratio, by assessing whether the pure interest expressed as a gravity equation between interests does not change after applying this spread. Results show that the mobile-ratio is the specification of the spread with no distortions on investment decisions. Regarding fiscal policy, this ratio plays a key role for both the Financial Transaction Tax and the VAT on financial services.